The Grape VlWRKY3 Gene Promotes Abiotic and Biotic Stress Tolerance in Transgenic Arabidopsis thaliana - Guo, Rongrong; Qiao, Hengbo; Zhao, Jiao; Wang, Xianhang; Tu, Mingxing; Guo, Chunlei; Wan, Ran; Li, Zhi; Wang, Xiping (Frontiers in Plant Science, 2018)
WRKY transcription factors are known to play important roles in plant responses to various abiotic and biotic stresses. The grape WRKY gene, WRKY3 was previously reported to respond to salt and drought stress, as well as methyl jasmonate and ethylene treatments in Vitis labrusca×V. vinifera cv. ‘Kyoho’. In the current study, WRKY3 from the ‘Kyoho’ grape cultivar was constitutively expressed in Arabidopsis thaliana under control of the cauliflower mosaic virus 35S promoter. The 35S::VlWRKY3 transgenic A. thaliana plants showed improved salt and drought stress tolerance during the germination, seedling and the mature plant stages. Various physiological traits related to abiotic stress responses were evaluated to gain further insight into the role of VlWRKY3, and it was found that abiotic stress caused less damage to the transgenic seedlings than to the wild-type plants. VlWRKY3 over-expression also resulted in altered expression levels of abiotic stress-responsive genes. Moreover, the 35S::VlWRKY3 transgenic A. thaliana lines showed improved resistance to Golovinomyces cichoracearum, but increased susceptibility to Botrytis cinerea, compared with the wild-type plants. Collectively, these results indicate that VlWRKY3 plays important roles in responses to both abiotic and biotic stress, and modification of its expression may represent a strategy to enhance stress tolerance in crops.